Malignant Melanoma of Small Bowel: A Rare Case - Kamal Bandhate; Ashok Kumar Diwan; Subeera Khan (Asian Journal of Medical Research, 2020)
Melanomas affecting the small bowel are usually metastasis from primary cutaneous lesions. A primary melanoma of the gastrointestinal tract is very rare with reported incidence of just 3%. We present a case of small bowel melanoma with liver metastases. Primary malignant melanoma of the small intestine is quite rare with only a few cases reported in literature. Like its cutaneous counterpart, intestinal melanomas too remains an aggressive disease with a poor prognosis. The overall survival of malignant melanoma affecting the GI tract is 4 to 6 months with a survival rate of less than 10% at 5 years.